Effects of Tool Pin Design on Formation of Defects in Dissimilar Friction Stir Welding. (2016) - Mehta, Kush P.; Badheka, Vishvesh J.
Abstract: Friction stir welding is an automatic process, falls under the category of solid state welding processes. In this study, friction stir welding was carried out on dissimilar copper to aluminum materials by nine different tool designs. Present investigation provides an insight on formation of defects under the effect of different tool pin designs. The tool pin profiles such as cylindrical, triangular, square and hexagonal were used in the present experimental investigation by keeping other parameters constant. These tool pin profiles were designed based on its static and dynamic constant areas from best suitable cylindrical profile. Besides, the defects were analyzed through visual observation, macrostructure, microstructural investigation and scanning electron microscope. The results revealed that, the copper particles detached from base material were large and irregular in case of polygonal pin designs. Maximum irregular and large copper particles were reported in welds made by triangular pin profiles. Additionally, polygonal pin profiles were generating defects such as voids, tunnel, cracks and fragmental defects irrespective of its static and dynamic constant areas. Furthermore, defects were decreased as the polygonal edges increases. Defect free macro joint was reported for cylindrical tool pin profile.